2017
DOI: 10.1016/j.micres.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Bead-based flow-cytometry for semi-quantitative analysis of complex membrane vesicle populations released by bacteria and host cells

Abstract: During infection, the release of nano-sized membrane vesicle is a process which is common both for bacteria and host cells. Host cell-derived membrane vesicles can be involved in innate and adaptive immunity whereas bacterial membrane vesicles can contribute to bacterial pathogenicity. To study the contribution of both membrane vesicle populations during infection is highly complicated as most vesicles fall within a similar size range of 30-300nm. Specialized techniques for purification are required and often … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Throughout the EV isolation procedures, samples were taken to determine the efficiency of isolation by CD63 + CD81 + bead-coupled flow cytometry 25 . Unfiltered and 0.22 µm-filtered conditioned media, as well as SEC-fractions and UF flow-throughs were assessed undiluted, while UF concentrates and final EV isolates from the UF-SEC, UC or UC-wash methods were diluted to the volume from which they were isolated.…”
Section: Methodsmentioning
confidence: 99%
“…Throughout the EV isolation procedures, samples were taken to determine the efficiency of isolation by CD63 + CD81 + bead-coupled flow cytometry 25 . Unfiltered and 0.22 µm-filtered conditioned media, as well as SEC-fractions and UF flow-throughs were assessed undiluted, while UF concentrates and final EV isolates from the UF-SEC, UC or UC-wash methods were diluted to the volume from which they were isolated.…”
Section: Methodsmentioning
confidence: 99%
“…As exosomes are generally smaller than the resolution limit of conventional optical techniques (light microscopy, flow cytometry scatter) (Van Der Pol et al 2010), highly dedicated technology is required for their detection, including electron microscopy, nanoparticle tracking analysis (NTA) (Sokolova et al 2011), tunable resistive pulse sensing (TRPS) (Maas, De Vrij, and Broekman 2014), and fluorescence-triggered high-resolution flow cytometry (Nolte- 'T Hoen et al 2012). Alternatively, exosomes may be characterized by bulk analysis techniques, such as Western blotting or bead-based flow cytome- try, a technique in which EV are linked to large beads and subsequently stained for exosome marker proteins (Suarez et al 2017;Volgers et al 2017). The most common method for isolation of exosomes is ultracentrifugation at 100,000 × g (Gardiner et al 2016).…”
Section: Exosomesmentioning
confidence: 99%
“…To overcome such issues, relatively simple bead-based protocols relying on the capture of EVs on antibody-coated beads with flow cytometric read-outs have been used to probe for the presence of candidate EV surface markers ( 22 , 41 45 ). Of note, a recent validation study of a bead-based protocol showed a clear correlation between mean fluorescence intensities and EV contents ( 46 ).…”
Section: Introductionmentioning
confidence: 99%